Pelatihan Interaktif Manajemen Layanan Tamu dan Fasilitas Homestay Berbasis Kearifan Lokal di Desa Leuwimalang - Purnamasari , Mita (Politeknik Sahid, 2025)
ABSTRACT conducted in Leuwimalang Tourism Village on July 24, 2025, involving 20 homestay owners. The training aimed to enhance participants’ capacity in housekeeping and sanitation according to hotel industry standards, while preserving local cultural values. The training methods included live demonstrations, guided practice, interactive discussions, and education on Guest Reception, Reservation Recording and Administration, Room and Facility Management, Delivery of Local Tourism Information, and Service Ethics Based on Local Wisdom. Evaluation was carried out using both quantitative and qualitative approaches, including pre-tests and post-tests, practical observations, sanitation checklists, as well as interviews and participant satisfaction questionnaires. Quantitative results showed an average increase in participants’ knowledge scores from 56.6% in the pre-test to 84.3% in the post-test, representing an average improvement of 27.7%. Practical observations and sanitation checklists indicated significant improvements in the application of cleanliness and sanitation standards, with 90% of participants meeting the minimum standards in housekeeping. Qualitatively, participants also demonstrated increased awareness of the importance of local wisdom in homestay services and post-pandemic hygiene protocols. This training contributed to improving the quality of homestay services in Leuwimalang Village, which is expected to enhance competitiveness and tourist satisfaction. Continued training and ongoing mentoring are recommended to sustain the capacity development of homestay operators. Keywords: homestay management, sanitation training, local wisdom, community-based tourism, capacity building ABSTRAK Pelatihan Interaktif Manajemen Layanan Tamu dan Fasilitas Homestay Berbasis Kearifan Lokal di Desa Wisata Leuwimalang dilaksanakan pada 24 Juli 2025 dengan melibatkan 20 pemilik homestay. Pelatihan bertujuan meningkatkan kapasitas peserta dalam aspek housekeeping dan sanitasi sesuai standar industri perhotelan, sekaligus mempertahankan nilai budaya lokal. Metode pelatihan yang digunakan mencakup demonstrasi langsung, praktik terbimbing, diskusi interaktif, dan penyuluhan Penerimaan Tamu (Guest Reception), Pencatatan dan Administrasi Reservasi, Pengelolaan Kamar dan Fasilitas, Penyampaian Informasi Wisata Lokal. Etika Pelayanan Berbasis Kearifan Lokal. Evaluasi dilakukan menggunakan pendekatan kuantitatif dan kualitatif, termasuk pre-test dan post-test, observasi praktik, checklist sanitasi, serta wawancara dan kuesioner kepuasan peserta. Hasil kuantitatif menunjukkan peningkatan rata-rata skor pengetahuan peserta dari 56,6% pada pre-test menjadi 84,3% pada post-test, dengan peningkatan rata-rata sebesar 27,7%. Observasi praktik dan checklist sanitasi memperlihatkan perbaikan signifikan dalam penerapan standar kebersihan dan sanitasi, dengan 90% peserta mencapai standar minimal dalam aspek housekeeping. Secara kualitatif, peserta juga mengalami peningkatan kesadaran akan pentingnya kearifan lokal dalam layanan homestay dan protokol kebersihan pascapandemi. Pelatihan ini berkontribusi pada peningkatan kualitas layanan homestay di Desa Leuwimalang yang diharapkan dapat meningkatkan daya saing dan kepuasan wisatawan. Disarankan pelatihan lanjutan dan pendampingan berkelanjutan untuk menjaga keberlanjutan peningkatan kapasitas pengelola homestay.. Kata kunci: manajemen homestay, pelatihan sanitasi, kearifan lokal, pariwisata berbasis masyarakat, peningkatan kapasitas